2014
DOI: 10.1159/000360093
|View full text |Cite
|
Sign up to set email alerts
|

Assessment with Unenhanced MRI Techniques of Renal Morphology and Hemodynamic Changes during Acute Kidney Injury and Chronic Kidney Disease in Mice

Abstract: Background/Aims: Changes in renal oxygenation and perfusion have been identified as common pathways to the development and progression of renal disease. Recently, the sensitivity of hemodynamic response imaging (HRI) was demonstrated; this is a functional magnetic resonance imaging (MRI) method combined with transient hypercapnia and hyperoxia for the evaluation of renal perfusion and vascular reactivity. The aim of this study was to utilize HRI for the noninvasive evaluation of changes in renal hemodynamics a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 39 publications
0
18
0
Order By: Relevance
“…We are not aware of any published reports of renal vascular structure in adenine‐induced CKD. However, Milman and colleagues recently provided evidence of blunted perfusion and renal vascular reactivity in anaesthetised mice with adenine‐induced CKD, using a magnetic resonance imaging technique for assessing the renal vascular response to hyperoxia . Consistent with these observations, renal blood flow measured directly by transit‐time ultrasound flowmetry or electromagnetic flowmetry under anaesthesia, and by the clearance of para‐aminohippurate in the conscious state, has been observed to be less in rats with adenine‐induced CKD compared to control animals.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…We are not aware of any published reports of renal vascular structure in adenine‐induced CKD. However, Milman and colleagues recently provided evidence of blunted perfusion and renal vascular reactivity in anaesthetised mice with adenine‐induced CKD, using a magnetic resonance imaging technique for assessing the renal vascular response to hyperoxia . Consistent with these observations, renal blood flow measured directly by transit‐time ultrasound flowmetry or electromagnetic flowmetry under anaesthesia, and by the clearance of para‐aminohippurate in the conscious state, has been observed to be less in rats with adenine‐induced CKD compared to control animals.…”
Section: Discussionmentioning
confidence: 88%
“…Consequently, we require experimental models of CKD in which pathological changes in renal tissue develop rapidly in response to a defined stimulus. Administration of adenine, either in food or by oral gavage, has been shown to result in reproducible renal dysfunction. Adenine is metabolised to 2,8‐dihydroxy‐adenine which forms crystalline casts within the renal tubules.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, in an experimental model, renal blood flow in rats with normal renal function temporarily decreased after exposure to contrast media, whereas in those with impaired renal function, the renal blood flow did not decrease . Indeed, several experimental studies have shown attenuated functional derangement against acute structural damages, including hypoxic stress, in CKD, and a recent experimental study using magnetic resonance imaging demonstrated less haemodynamic change following hypoxic stress in mice models of CKD than in normal mice . Further research is therefore needed to evaluate the differing renal artery responses to iodinated contrast media in patients with both normal and impaired kidney function.…”
Section: Discussionmentioning
confidence: 99%
“…Although a lower corticomedullary sodium gradient has been demonstrated in kidney allografts in comparison to native kidneys, sodium imaging has neither been able to reflect kidney function in kidney transplantation patients (Moon et al, 2014), nor in healthy individuals with a variety of eGFRs (Haneder et al, 2013), and is therefore not discussed in detail. However, it must be pointed out that preliminary experimental results in other kidney disease states, such as acute tubular necrosis, have shown changes in sodium imaging (Maril et al, 2006; Atthe et al, 2009), Similar to sodium MRI, hemodynamic response imaging has only been applied in experimental settings in animals thus far (Milman et al, 2013, 2014) .…”
Section: Conventional Vs Functional Mri For the Assessment Of Subclimentioning
confidence: 99%
“…In this way hemodynamic changes due to Bohr-effect and CO 2 -induced vasodilation are provoked, for instance in the kidney, which enables evaluation of regional vascular reactivity. To date, only two studies in experimental animals have investigated kidney HRI (Milman et al, 2013, 2014). …”
Section: Clinical Experience With Functional Mri In Kidney Allograftsmentioning
confidence: 99%